Russia and the South Caucasus: The China Challenge. Issue 9 (21st October 2022) - German, Tracey
Abstract: Russia has sought to maintain its influence in the South Caucasus by a variety of means, viewing the region as an area of crucial importance for its core strategic interests. However, China's prominence in the South Caucasus has increased significantly over the past decade, as the South Caucasus states seek to diversify their diplomatic and economic ties. This essay explores whether Russia's regional hegemony in the South Caucasus is being challenged by China: does China's growing engagement with the states of the South Caucasus pose a challenge to Russian influence within its traditional zone of 'privileged interest'?